The Discourse of Capitalist Class and Public Policy in the Handling of COVID-19 Pandemic in Indonesia - Bahar, Adam Amin; Marijan, Kacung; Mardiyanta, Antun (UI Scholars Hub, 2021)
In the early period of handling the COVID-19 pandemic in Indonesia, the Indonesian government prioritized the economy and health sectors. This study argues that these government actions and policies are heavily influenced by discourse from the capitalist class. This study aims to discuss the articulation of several different discursive elements of the capitalist class in the early period of handling the COVID-19 pandemic in Indonesia and its impact on public policy. This study focuses on two capitalist classes, namely medical and non-medical capitalists. This study found that the discursive elements from the government on these two significant issues had in common with the discursive elements of these two capitalist classes. The discourse of public discipline over the use of medical products from medical capitalists had the same discursive elements as that of government discourse. Both of them articulated this discourse with the aim of public health, but theoretically, this is important to increase the accumulation of capital in the health industry in the future. Another group of capitalists, however, generally see this pandemic as a disaster and an obstacle to continue their capital accumulation. Therefore, the central discourse that was raised by this group was the economic impact of this pandemic. Although these two discourses are different, this study found that they are not contradictory but rather complementary. The discourse spread by the two capitalist classes influenced state policy in dealing with COVID-19 in Indonesia significantly. This study emphasizes the importance of the discourse articulation of the capitalist class in the politics of policymaking, especially in Indonesia.